Measurement and estimation of transpiration of a soilless rose crop and application to irrigation management - Suay, Ricardo; Martínez, Pedro F.; Roca, Dolors; Martínez, M.; Herrero, J. M.; Ramos, Carlos (2017)
Current irrigation practices in protected soilless culture, are based either on fixed interval scheduling, corrected by means of EC monitoring in drainage or substrate extract, or on crop transpiration estimations by means of solar radiation integration. A study has been carried out, where the transpiration of a heated rose crop, conducted by the shoot bending system, is continuously measured by means of an electronic balance, and estimations are calculated with a simplified Penman-Monteith equation, adjusted by weekly LAI estimations, as well as outside solar radiation and inside water vapour saturation deficit recordings. Based on these transpiration estimations, an irrigation strategy has been tested and compared to current irrigation practices used in commercial holdings.